Th, U AND Pb ANALYTICAL DATA AND CHIME DATING OF MONAZITES FROM METAMORPHIC ROCKS OF THE RAYNER, LUTZOW-HOLM, YAMATO-BELGICA AND SØR RONDANE COMPLEXES, EAST ANTARCTICA - アサミ, マサオ; スズキ, カズヒロ; アダチ, マモル; ASAMI, Masao; SUZUKI, Kazuhiro; ADACHI, Mamoru (National Institute of Polar Research, 1997)
P(論文) This is a data-set paper, listing a total of 1091 electron microprobe ThO_2,UO_2 and PbO analyses and CHIME ages of monazites from 12 granulite-facies paragneiss samples from Mt. Vechernyaya (west-coastal Rayner Complex, 2 samples), Syowa Station (Lutzow-Holm Complex, 2 samples), the Yamato Mountains (Yamato-Belgica Complex, 2 samples) and the S∅r Rondane Mountains (Sør Rondane Complex, 6 samles), East Antarctica. Most monazite grains are chronologically unzoned. They occur in garnet as well as in other main constituent minerals and at grain-boundaries. The CHIME ages are within a narrow range : 533±9 Ma (MA88021504B) and 532±9 Ma (MA88021515-2) at Mt. Vechernyaya, 533±10 Ma (MA80020603B) and 537±9 Ma (MA80020702) at Syowa Station, 534±7 Ma (Y80A119) and 531±8 Ma (Y80A121d) in the Yamato Mountains, and 534±10 Ma (MA88011002-1), 529±14 Ma (MA88012216), 543±18 Ma (MA88020202-1), 542±6 Ma (84021904B), 539±16 Ma (84022004) and 541±15 Ma (85020401C) in the Sør Rondane Moutains. Distinct stepwise age zoning is observed in some grains from samples from the Yamato Mountains (Y80121d) and Sør Rondane Mountains (MA88020202-1,84021904B and 84022004). The zoned grains, like the unzoned ones, occur in garnet as well as in other main constituent minerals and at grain-boundaries. The rims of the zoned monazite grains give CHIME ages of 530-550 Ma, almost the same as those of unzoned grains, but the CHIME ages of the cores range from ca. 620 to ca. 750 Ma. The intergrain variation in the core age within a single sample suggests that the older cores are of detrital origin; the paragneiss protolith, at least in the Yamato-Belgica and Sør Rondane Complexes, is considered to have been deposited after the ～620 Ma thermal event in the provenance. This demonstrates that these paragneisses, if not all, are not of the polymetamorphosed late Proterozoic complexes as so far believed. The post～620 Ma sediments, along with the protolith in the west-coastal Rayner and Lutzow-Holm Complexes, are likely to have undergone high-grade ...